Gut microbiome-mediated modulation of hepatic cytochrome P450 and P-glycoprotein: impact of butyrate and fructo-oligosaccharide-inulin. (26th April 2020) - Walsh, Jacinta; Gheorghe, Cassandra E; Lyte, Joshua M; van de Wouw, Marcel; Boehme, Marcus; Dinan, Timothy G; Cryan, John F; Griffin, Brendan T; Clarke, Gerard; Hyland, Niall P
Abstract: Objectives: Our objective was to demonstrate microbial regulation of hepatic genes implicated in drug metabolism and transport using germ-free (GF) mice and to explore the impact of a microbial metabolite, butyrate, and a prebiotic dietary intervention on hepatic gene expression in mice. Methods: Using reverse-transcriptase PCR, we investigated cytochrome P450 (CYP) and multidrug-resistance protein 1 (MDR1) expression in conventional, GF and colonised GF mice. To investigate the effects of butyrate, sodium butyrate (3 g/l) was administered for 21 days to conventional or GF mice. In the prebiotic study, young adult and middle-aged mice received diet enriched with 10% fructo-oligosaccharide (FOS)-inulin for 14 weeks. Key findings: Colonisation of GF animals normalised expression of Cyp3a11 and Mdr1b to conventional levels. Butyrate upregulated Cyp2b10 in conventional mice ( P < 0.05) but overall did not induce widespread changes in hepatic genes. FOS-inulin increased Cyp3a13 expression and had the opposite effect on Mdr1a expression in young adult mice ( P < 0.05). Age, on the other hand, influenced the prebiotic effect on Cyp2a4 expression ( P < 0.01). Conclusion: The expression of hepatic genes implicated in drug metabolism and transport displays sensitivity to the microbiome, microbiome-derived metabolites and a microbial-targeted intervention. Our study may provide the impetus to explore microbiota-targeted interventions in normalising host metabolic activity and reducing inter-individual variability in drug pharmacokinetics.